Synergistic effect of interleukin‐17 and tumour necrosis factor‐α on inflammatory response in hepatocytes through interleukin‐6‐dependent and independent pathways. (31st May 2018) - Beringer, A.; Thiam, N.; Molle, J.; Bartosch, B.; Miossec, P.
Summary: The proinflammatory cytokines interleukin (IL)‐17 and tumour necrosis factor (TNF)‐α are targets for treatment in many chronic inflammatory diseases. Here, we examined their role in liver inflammatory response compared to that of IL‐6. Human hepatoma cells (HepaRG, Huh7.5 and HepG2 cells) and primary human hepatocytes (PHH) were cultured with IL‐6, IL‐17 and/or TNF‐α. To determine the contribution of the IL‐6 pathway in the IL‐17/TNF‐α‐mediated effect, an anti‐IL‐6 receptor antibody was used. IL‐17 and TNF‐α increased in synergy IL‐6 secretion by HepaRG cells and PHH but not by Huh7.5 and HepG2 cells. This IL‐17/TNF‐α synergistic cooperation enhanced the levels of C‐reactive protein (CRP) and aspartate aminotransferase (ASAT) in HepaRG cell and PHH cultures through the induction of IL‐6. IL‐17/TNF‐α also up‐regulated IL‐8, monocyte chemoattractant protein (MCP)‐1 and chemokine (C‐C motif) ligand 20 (CCL20) chemokines in synergy through an IL‐6‐independent pathway. Interestingly, first exposure to IL‐17, but not to TNF‐α, was crucial for the initiation of the IL‐17/TNF‐α synergistic effect on IL‐6 and IL‐8 production. In HepaRG cells, IL‐17 enhanced IL‐6 mRNA stability resulting in increased IL‐6 protein levels. The IL‐17A/TNF‐α synergistic effect on IL‐6 and IL‐8 induction was mediated through the activation of extracellular signal‐regulated kinase (ERK)‐mitogen‐activated protein kinase, nuclear factor‐κB and/or protein kinase B (Akt)–phosphatidylinositol 3‐kinase signalling pathways. Therefore, the IL‐17/TNF‐α synergistic interaction mediates systemic inflammation and cell damage in hepatocytes mainly through IL‐6 for CRP and ASAT induction. Independently of IL‐6, the IL‐17A/TNF‐α combination may also induce immune cell recruitment by chemokine up‐regulation. IL‐17 and/or TNF‐α neutralization can be a promising therapeutic strategy to control both systemic inflammation and liver cell attraction. Abstract : IL‐17 and TNFα have synergistic interactions on cytokine production by hepatocytes, with IL‐17 acting first to increase the effect of TNFα. IL‐17 and TNFα induce CRP through the induction of IL‐6. IL‐17 and TNFα induce chemokine production independently of IL‐6.